Republic of Montenegro : 2008 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Republic of Montenegro. (IMF Staff Country Reports; Country Report ;, 2009)
This 2008 Article IV Consultation highlights that Montenegro has made significant progress in overhauling its economy. The authorities have taken several welcomed steps to help strengthen financial sector stability. Executive Directors have welcomed the structural reforms implemented over the past few years and financial integration that have helped Montenegro attract substantial foreign direct investment and generate rapid growth with moderate inflation. Directors have also supported the authorities' actions to bolster financial system stability and reduce vulnerabilities by intensifying supervisory oversight, tightening prudential regulations, and lifting bank capitalization requirements.